The Effect of Regeneration and External Knowledge on Business Survival Through Innovation Practices as Intervening Variables in MSME Crackers in Tanggulangin, Sidoarjo Regency - Sahda Zerlinda; Muhadjir Anwar; Arief Bachtiar (Indonesian Journal of Business Analytics, 2025)
This study examines the impact of regeneration and external knowledge on business sustainability in the Tanggulangin cracker MSME in Sidoarjo Regency, by implementing innovation practices as a modification. This study uses a quantitative research approach and asks questions to 65 respondents who are MSME actors who have a perspective on the business regeneration succession process and regularly participate in training activities organized by the local government. By using SmartPLS 4.0 to analyze the data, the findings show that regeneration and external knowledge have a significant positive effect on business sustainability. This finding is consistent with the Theory of Planned Behavior, which states that intention is a function of three determinants: the first is personal, the second reflects social influences, and the third is related to control with problems. Intention plays a unique role in directing action, serving as a link between a person's deep beliefs and desires and specific actions.